The THE CONCEPTUALIZATION OF WOMEN IN THE NOVEL BY PRAMOEDYA ANANTA TOER: A COGNITIVE SEMANTIC STUDY: KONSEPTUALISASI PEREMPUAN DALAM NOVEL KARYA PRAMOEDYA ANANTA TOER: SUATU KAJIAN SEMANTIK KOGNITIF - Uzair Uzair; Wagiati Wagiati; Hera Meganova Lyra (LLDIKTI Wilayah X, 2023)
The purpose of this study is to examine the conceptualization of women and image schemes in novels written by Pramoedya Ananta Toer. The approach in this main research is the cognitive semantics of Lakoff and Johnson (2009) which is reinforced by Knowles & Rosamund (2006) and Kovecses (2010) and the image schema of Cruse and Croft (2004). The method used in this research is a qualitative descriptive method. The data collected focuses on women's conceptual metaphor data. Based on the analysis, researchers find nine conceptual metaphors for women, namely: (1) the concept of objects; (2) plant concept; (3) position concept; (4) animal concept; (5) the concept of the sense of taste; (6) the concept of the sense of touch; (7) the concept of the sense of sight; (8) state concept; and (9) building concept. The research finds five image schemes (1) container; (2) existence; (3) identity; (4) force; and (5) space.